Fantastic beast and where to find them the beast: cinematic guide - BAKER, FELICITY; FELICITY BAKER (NY Scholastic Inc, 2017)
a, illustrated companion book that profiles the magical creatures featured in the 2016 film.
Keywords: Released by Scholastic, it serves as a visual, and educational guide to the creatures Newt Scamander carries in his case; empathy, the danger of prejudice, and the importance of conservation